KRT23 SEBAGAI BIOMARKER PROGNOSTIK PADA ADENOKARSINOMA REKTAL: ANALISIS BIOINFORMATIKA BERBASIS UALCAN: KRT23 sebagai Biomarker Prognostik pada Adenokarsinoma Rektal: Analisis Bioinformatika Berbasis UALCAN - Danang Prasetyaning Amukti; Mitha Dwi Puspitasari; Ari Widhiarso; Bayu Bakti Angga Santoso; Ria Indah Pratami (Program Studi Farmasi, Universitas Muhadi Setiabudi, 2026)
Introduction: Colorectal cancer, including READ, is one of the leading causes of cancer death worldwide. Recent studies have shown the involvement of the KRT23 gene, a member of the type I keratin family, in various malignant processes, including tumor cell proliferation, migration, and invasion. Although KRT23 expression has been studied in several types of cancer, its role in rectal cancer remains poorly understood. This study aimed to evaluate the relationship between KRT23 expression and patients' clinical characteristics and their survival. Methods: KRT23 expression data in rectal cancer patients were obtained from the UALCAN platform, which included subgroups based on race, sex, and weight status. Analysis was performed to evaluate the relationship between KRT23 expression levels and patients' clinical characteristics and their effects on survival using Kaplan-Meier curves and log-rank statistical analysis. Results: KRT23 expression was significantly increased in rectal cancer tissues compared to normal tissues. Survival analysis showed that race significantly affected the relationship between KRT23 expression and patient prognosis (p < 0.0001), especially in the Caucasian and African-American racial groups. In contrast, there was no significant difference based on gender (p = 0.97) and weight status (p = 0.64). Conclusion: High KRT23 expression is associated with better prognosis in certain racial subgroups, making it a potential candidate prognostic biomarker for rectal cancer. However, further studies with larger sample sizes are needed to strengthen these findings and understand the underlying biological mechanisms.